Hydrobiogeochemical Controls on the Delivery of Dissolved Organic Matter to Boreal Headwater Streams - J. Alan Roebuck Jr.; Karen Prestegaard Jr.; Christian Gaviria; Allison Myers‐Pigg; Susan E. Ziegler (Water Resources Research)
Abstract Understanding controls on the delivery of dissolved organic matter (DOM) from terrestrial to aquatic systems is key for constraining carbon balances and fluxes in boreal headwater catchments. The largest export of DOM generally occurs during intense periods of water delivery to the landscape (e.g., rain events); however, the timing and magnitude of DOM is complicated by geomorphological, hydrometeorological, and biogeochemical variability. To better assess mechanisms controlling the delivery of DOM to boreal streams, DOM was investigated in two morphologically distinct catchments of an experimental forest watershed in western Newfoundland, one dominated by low relief wetlands and the other by steep hillslopes. The DOM was compared during two fall storms of similar magnitude but contrasting moisture conditions during the autumn transition. Variable concentrations and optical character highlighted antecedent conditions are important for the delivery of DOM to boreal streams. Concentration‐discharge relationships with stream hydrograph separation analysis suggest preferential flowpaths through shallow mineral horizons as a key pathway for delivery of DOM in the hillslope dominated catchment compared to rapid input from near‐stream wetlands in the low relief catchment. Loss of DOM via preferential pathways suggests an additional mechanism for surface soil carbon loss not directly informed by lateral flow and soil hydrology, which has important implications for our conceptualization and modeling of carbon fluxes in boreal systems. These results suggest watershed scale responses of DOM in boreal headwater catchments are complex, and better linkages between catchment scale hydrology and landscape hydrobiogeochemistry are required to constrain terrestrial to aquatic carbon fluxes in boreal landscapes.